The features of the Russian banking sector transformation - Tatuev, Arsen A.; Shanin, Sergey A.; Lyapuntsova, Elena V.; Rokotyanskaya, Violetta V.; Galiuta, Oksana N. (Opción, 2019)
The purposes of work are to reveal the modern characteristics of the transformation of the banking system, taking into account the function of a financial intermediary in the economy via statistical analysis of proportions. Analytical and theoretical results of the study showed that the structure of the banking sector of the national economy will be determined not so much by the criteria of profitability as by new organizational, managerial and financial technologies. In conclusion, In order to effectively develop banking activities, the main attention should be paid to a large number of systemic advantages of cryptographic blockchain technology.